Peritoneal chemotherapy delivery systems for ovarian cancer treatment: systematic review of animal models - Simonsen, Marcelo; Mendoza López, Rossana Verónica; Maistro, Simone; Ikeoka, Lucas Takeshi; Pereira, Glaucia Fernanda de Lima; Lugão, Ademar Benévolo; Sadalla, José Carlos; Katayama, Maria Lúcia Hirata; Folgueira, Maria Aparecida Azevedo Koike (Frontiers in Oncology, 2025)
IntroductionIntraperitoneal chemotherapy for ovarian cancer treatment has controversial benefits as most methodologies are associated with significant morbidity. We carried out a systematic review to compare tumor response, measured by tumor weight and volume, between intraperitoneal chemotherapy delivered via drug delivery systems (DDSs) and free intraperitoneal chemotherapy in animal models of ovarian cancer. The secondary aim was to assess the toxicity of DDS-delivered chemotherapy, based on changes in animal body weight.MethodsBased on PRISMA and SYRCLE guidelines, we identified 38 studies for review, of which 20, were used in the meta-analysis. We evaluated outcome, through tumor volume and tumor weight and, toxicity, through animal weight. Analysis was based on drugs employed and treatment duration.ResultsMost studies were performed on mice. Ovarian cancer cell lines most commonly used to induce xenografts were SKOV3 (19 studies) and A2780 (6 studies). Intraperitoneal device, also known as drug delivery systems (DDS), consisted in nanoparticles, hydrogels, lipid polymer and others. The most commonly used drugs were paclitaxel and cisplatin. Most studies used as the control treatment the same chemotherapy applied free intraperitoneally and tumor response/animal weight were evaluated weekly. There was a small benefit in overall tumor reduction in animals treated with intraperitoneal chemotherapy applied through the slow release device compared with animals treated with intraperitoneal free chemotherapy, as evaluated through tumor weight - results in standardized mean difference. (-1.06; 95% CI: -1.34, -0.78) and tumor volume (-3.72; 95% CI: -4.47, -2.97), a benefit that was seen in most weekly evaluations and for most chemotherapy drugs, such as carboplatin (tumor weight: -5.60; 95% CI: -7.83, -3.37), paclitaxel (tumor weight: -1.18; 95% CI: -1.52, -0.83), and cisplatin (tumor volume: -2.85; 95% CI: -3.66, -2.04) carboplatin (tumor volume: -12.71; 95% CI: -17.35, -8.07); cisplatin (tumor volume: -7.76; 95% CI: -9.88, -5.65); paclitaxel (tumor volume: -2.85; 95% CI: -3.66, -2.04). Regarding animal weight, there was no weight reduction in animals treated with intraperitoneal chemotherapy applied through the slow-release device compared with animals treated with intraperitoneal free chemotherapy. However, significant heterogeneity was observed in some comparisons.Conclusionslow-release devices are overall safe and effective in animal models of ovarian cancer. It was not possible to evaluate which one is the most promising device to treat ovarian cancer, because many different types were used to apply chemotherapy intraperitoneally.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42021224573.